The Protective Effects of Adolescent Motherhood in South Central Appalachia: Salvation From Drugs and Emptiness. (September 2015) - Dalton, Elizabeth D.
This study qualitatively explored the meaning of teenage motherhood to young Appalachian mothers. Fourteen in-depth interviews at the homes of mothers between the ages of 18 and 22 from the South Central Appalachian region were conducted. Findings indicate that teenage motherhood is symbolically reproduced by filling a void and providing escape from the drug culture. Analysis of these findings indicates that the meaning of motherhood is characterized by salvation. This salvation is shaped by the emotional chasm that motherhood fills, as well as the protective barrier it provides between the mother and the surrounding drug culture. Implications of these findings might include a need to examine the protective effects of motherhood from negative sociocultural forces among other subcultures. Also, the pervasive drug culture that surrounds young people in Appalachia should be taken into consideration when shaping policy and interventions for teenage pregnancy prevention.